Potential use of antioxidants for the treatment of chronic inflammatory diseases - Blagov, Alexander V.; Summerhill, Volha I.; Sukhorukov, Vasily N.; Zhigmitova, Elena B.; Postnov, Anton Y.; Orekhov, Alexander N. (Frontiers in Pharmacology, 2024)
The excessive production of various reactive oxidant species over endogenous antioxidant defense mechanisms leads to the development of a state of oxidative stress, with serious biological consequences. The consequences of oxidative stress depend on the balance between the generation of reactive oxidant species and the antioxidant defense and include oxidative damage of biomolecules, disruption of signal transduction, mutation, and cell apoptosis. Accumulating evidence suggests that oxidative stress is involved in the physiopathology of various debilitating illnesses associated with chronic inflammation, including cardiovascular diseases (CVDs), diabetes, cancer, or neurodegenerative processes, that need continuous pharmacological treatment. Oxidative stress and chronic inflammation are tightly linked pathophysiological processes, one of which can be simply promoted by another. Although, many antioxidant trials have been unsuccessful (some of the trials showed either no effect or even harmful effects) in human patients as a preventive or curative measure, targeting oxidative stress remains an interesting therapeutic approach for the development of new agents to design novel anti-inflammatory drugs with a reliable safety profile. In this regard, several natural antioxidant compounds were explored as potential therapeutic options for the treatment of chronic inflammatory diseases. Several metalloenzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), are among the essential enzymes that maintain the low nanomolar physiological concentrations of superoxide (O2•-) and hydrogen peroxide (H2O2), the major redox signaling molecules, and thus play important roles in the alteration of the redox homeostasis. These enzymes have become a striking source of motivation to design catalytic drugs to enhance the action of these enzymes under pathological conditions related to chronic inflammation. This review is focused on several major representatives of natural and synthetic antioxidants as potential drug candidates for the treatment of chronic inflammatory diseases.